Gender and LGBTQ Issues in Election Processes Global and Local Contexts - Barczyszyn-Madziarz, Paulina; Żukiewicz, Przemysław (Taylor & Francis, 2022)
looks at issues on Gender and LGBTQ matters in political elections in both institutional and communication contexts. Examining wins and losses in elections and assessing accountabilities in those results this broad and international collection analyses how the issue of gender and LGBTQ identity is both factored into, and determines electoral success, not only in consolidated democracies such as the United States, New Zealand, and Norway, but also in a country facing an undemocratic turn such as Poland. . Does raising the subject of gender and LGBTQ issues affect electoral processes? Are there countries where gender and LGBTQ issues are more likely to be instrumentalised in the electoral process? Can common patterns between countries be detected? This book seeks to answer these questions and center gendered issues through a range of topics including party loyalty, voter participation, gendered media coverage, and discourses on electoral defeat, and leadership. This book is suitable for students and scholars in LGBTQ Studies, Politics, Social Sciences and Gender Studies.